Employing a failure criterion with interaction terms to simulate the progressive failure of carbon-epoxy laminates - Jamaluddin, Mahmud; Faris, Ismail, Prof. Dr.; Tasneem, Pervez, Assoc. Prof. Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/